EFEKTIVITAS PENGGUNAAN LKPD BERBASIS REFUTATION TEXT DALAM MEREMEDIASI MISKONSEPSI SISWA PADA MATERI SENYAWA HIDROKARBON - Gilbert Dwi Barasbanyu; Eny Enawaty; Lukman Hadi (Universitas Tanjungpura, Prodi Pendidikan Kimia, 2021)
This aims of this research is to determine whither there is a significant difference at of achievement between students before and after learning using refutation text based worksheet ant to effectiveness refutation text based worksheet on reducing misconceptions on topic hydrocarbon. The form of research used was pre-experimental with a one-group pretest-posttest research design. Samples were taken from class XI MIPA 4 which consisting of twenty nine students through purposive sampling technique. Data were collected using multiple choice diagnostic test with three alternative answers and three alternative reasons consisting of 15 questions. Acoarding to analusis, there is a differences in achievement between students were tested using the Wilcoxon test and an Pvalue who less the 0,000 which meant there was a significant difference. Acoarding to propotions test the effectiveness score 0,61 which was as category medium. Acoarding to analysis, there was a decrease in the percentage of students' concept errors by 47.4%. Conclude there is a significant different of achievement before and after remediation with medium effectiveness. Keywords: Effectiveness, Hydrocarbon Compounds, LKPD, Misconception, Refutation Text, Remediation